Disadvantaged Early-Life Socioeconomic Circumstances Are Associated With Low Respiratory Function in Older Age. (30th July 2018) - Cheval, Boris; Chabert, Clovis; Orsholits, Dan; Sieber, Stefan; Guessous, Idris; Blane, David; Kliegel, Matthias; Janssens, Jean-Paul; Burton-Jeangros, Claudine; Pison, Christophe; Courvoisier, Delphine S; Boisgontier, Matthieu P; et al.
Abstract: Background: Poor lung function in late life may stem from early-life risk factors, but the epidemiological evidence is inconsistent. We investigated whether individuals who experienced disadvantageous socioeconomic circumstances (SEC) in early life showed lower levels of respiratory function in older age, a steeper decline over time, and whether these relationships were explained by adult-life SEC, body mass index, and physical inactivity in older age. Methods: We used data from the Survey of Health Ageing and Retirement in Europe (2004–2015). Participants' peak expiratory flow (PEF) was assessed with a mini-Wright peak flow meter at second, fourth, and sixth waves. Confounder-adjusted linear mixed-effect models were used to examine the associations between early-life SEC and PEF in older age. A total of 21, 734 adults aged 50–96 years (46, 264 observations) were included in the analyses. Results: Older adults with disadvantaged early-life SEC showed lower levels of PEF compared with those with advantaged early-life SEC. The association between early-life SEC and late-life PEF persisted after adjusting for adult-life SEC, smoking, physical inactivity, and body mass index. PEF declined with age, but the effect of early-life SEC on this decline was not consistent across robustness and sensitivity analyses. Conclusions: Early life is a sensitive period for respiratory health. Further considering the effect of SEC arising during this period may improve the prevention of chronic respiratory diseases.